Early switch/early discharge opportunities for hospitalized patients with methicillin resistant Staphylococcus aureus complicated skin and soft tissue infections: Saudi Arabia and United Arab Emirates - Ashraf El Houfi; Abdulhakeem Al Thaqafi; Thamer H. Alenazi; Fayssal Farahat; Caitlyn T. Solem; Jennifer M. Stephens; Courtney Johnson; Cynthia Macahilig; Wing Yu Tang; Seema Haider (Elsevier, 2020)
Objectives: To describe opportunities for early switch (ES) from intravenous (IV) to oral (PO) antibiotics and early discharge (ED) of patients hospitalized in the Kingdom of Saudi Arabia (KSA) and the United Arab Emirates (UAE) with methicillin-resistant Staphylococcus aureus (MRSA) complicated skin and soft tissue infections (cSSTIs). Methods: This retrospective medical chart review study enrolled physicians from 16 KSA and UAE sites to collect data for 107 MRSA cSSTI patients. Results: Actual length of MRSA-active treatment was 13.3 ± 9.3 mean days in KSA and 11.2 ± 3.9 mean days in UAE, with a mean of 11.8 ± 9.3 days of MRSA-targeted IV therapy in KSA and 10.7 ± 4.3 days in UAE. 12.5% in KSA met ES criteria and potentially could have discontinued IV therapy 4.0 ± 2.9 days sooner; 44.0% in UAE could have discontinued 6.6 ± 3.6 days sooner. Patients were hospitalized for a mean 28.6 ± 45.0 days in KSA and 13.1 ± 5.9 days in UAE. 25.0% in KSA and 48.0% in UAE met ED criteria and potentially could have been discharged 6.1 ± 8.0 days earlier in KSA and 7.9 ± 5.0 days earlier in UAE. Conclusions: A significant proportion of patients hospitalized for MRSA cSSTI could be eligible for ES or ED opportunities, resulting in potential for reductions in IV and bed days.